The role of urological pathology in the development of terminal renal failure - Pavel A. Simonov; Mikhail A. Firsov; Daria A. Dunc; Eugene A. Bezrukov; Sergei V. Ivliev (ZAO "Consilium Medicum", 2022)
Background. Chronic kidney disease (CKD) is one of the most serious and pressing health problems worldwide today. The end stage of CKD leads to disability and dramatically reduces the quality of life, which is caused by the need for continuous renal replacement therapy. The causes of CKD are various and are often caused by urological pathology. Materials and methods. Five hundred eighty seven case histories of patients with CKD on renal replacement therapy in the Krasnoyarsk Territory for 2022 were analyzed. Most of them were patients with chronic glomerulonephritis (38%) and urological diseases (29%). Other reasons that led to hemodialysis are diabetic nephropathy (12%), hypertensive nephropathy (8%), mixed nephropathy (5%). Systemic diseases with kidney damage, oncological diseases, rejection of a kidney transplant, genetic diseases 2% each. Results. Оne hundred and seventy patients with urological diseases are on program hemodialysis. The mean age of this group of patients was 56.2 years. The incidence of CKD varies slightly between men (48%) and women (52%). The structure of the incidence of urological pathology is as follows: all patients somehow had signs of chronic pyelonephritis. Of 170 people, only 15% had primary chronic pyelonephritis as the main cause of end-stage CKD. The remaining 81% of patients showed signs of secondary pyelonephritis. Patients with polycystic kidney disease accounted for 44%, patients with urolithiasis 13%, patients with anomalies in the development of the kidneys and urinary tract 7%, vesicoureteral reflux, with prostate adenoma 5% patients with signs of a neurogenic bladder 3% and 3% patients with ureteral structure. Patients with oncological pathology accounted for 4%. Conclusion. Over the past decade, the structure of diseases of patients on hemodialysis has changed. Due to the more accessible diagnostic service in the region, the proportion of urological pathologies in patients is increasing. At the same time, the timely use of reconstructive, minimally invasive, nephron-sparing operations can reduce the risks of progression of CKD. However, the number of end-stage patients is steadily increasing, requiring continued development of the hemodialysis service and other forms of renal replacement therapy.